A dyciandiamine-based methacrylate-epoxy dual-cure blend-system for stereolithography - Romeis, Manuel; Drummer, Dietmar (Polymers, 2021)
In this research, an epoxy-based dual-cure system is developed and characterized for SLA additive manufacturing. Dual-cure systems consist of UV-curable acrylates and thermal active components. The second curing step offers an additional degree of freedom to design specific material properties. In this study, a blend of varying concentrations of an epoxy/curing agent mix, respectively, DGEBA, DICY and photocurable methacrylate, was used to create a material that is printable in the SLA process into a UV-cured or green part and subsequently thermally cured to achieve superior thermal and mechanical properties. Calorimetric measurements were performed to determine the reactivity of the thermal reaction at different concentrations of epoxy. The fully cured specimens were tested in mechanical and dynamic mechanical measurements, and the results showed a significant improvement in tensile stress and glass transition temperature with rising epoxy concentrations. Fractured surfaces from tensile testing were investigated to further characterize the failure of tested samples, and thermal degradation was determined in TGA measurements, which showed no significant changes with an increasing epoxy concentration.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Additive manufacturing (AM); Dual-cure; Stereolithography (SLA)